2014
DOI: 10.1007/s12029-014-9585-z
|View full text |Cite
|
Sign up to set email alerts
|

Time to Adjuvant Therapy and Other Variables in Localized Gastric and Gastroesophageal Junction (GEJ) Cancer (IJGC-D-13-00162)

Abstract: Only about one third of patients who received adjuvant therapy were treated within 56 days of surgery. Although stages III and IVM0 and older age were associated with inferior outcome, delay in adjuvant therapy was not associated with inferior survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…20 Multi-modality treatment of proximal gastric cancer has been shown to improve outcomes but delays from surgical complications have been shown to lead to delays in adjuvant therapy as well as increased rates of early recurrence. 12,13,21 In patients with significant comorbidities who are more likely to experience surgical complications, selection of the least morbid approach that will achieve an R0 resection is paramount to improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Multi-modality treatment of proximal gastric cancer has been shown to improve outcomes but delays from surgical complications have been shown to lead to delays in adjuvant therapy as well as increased rates of early recurrence. 12,13,21 In patients with significant comorbidities who are more likely to experience surgical complications, selection of the least morbid approach that will achieve an R0 resection is paramount to improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11 Approach-associated morbidity rates are important, as complications from surgical resection of proximal gastric cancer can lead to delays in adjuvant therapy, which adversely affect oncologic outcomes. [12][13][14][15] The aim of this study was to characterize the short-term morbidity and mortality associated with various surgical approaches utilized to resect malignancies of the gastric cardia. Additionally, this study sought to characterize risk factors for morbidity and mortality that are common to patients undergoing resection of a gastric cardia malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have addressed the effect of the recovery period following curative surgery and start of adjuvant therapy as potential contributors to outcome in other cancers including breast , colorectal , and gastric . In breast cancer, there were conflicting reports, with no difference in disease‐free survival or OS in patients who received adjuvant chemotherapy within the arbitrary cut‐off of 21 days after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Results for gastric cancer have been inconclusive. While treatment before 8 weeks was associated with a trend towards improved relapse‐free survival and OS , a population‐based analysis found that an 8‐week cut off for receipt of AT did not affect disease‐free survival . Thus, one can see a trend in oncologic literature favoring “timely” initiation of AT but with no consensus regarding what is “early” and what is “late.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation